4CPS-291 Palbociclib: early neutropenia as a pharmacodynamic marker in a real world setting?. (14th March 2021) - Fernández-Sala, X; Navarrete-Rouco, ME; Río-No, L; Albanell, J; Conde-Estévez, D
Abstract : Background and importance: The most frequent adverse effect of palbociclib is neutropenia, resulting in dose reductions and treatment interruptions. Recently, it has been reported that early palbociclib related neutropenia was associated with a prolonged progression free survival (PFS) 1 . However, there are no analysis data based on the real world setting, outside of clinical trials. Aim and objectives: To determine whether early neutropenia in our cohort of patients was associated with disease response to palbociclib combined with fulvestrant or an aromatase inhibitor. Material and methods: This was a retrospective study including all patients who started treatment with palbociclib between December 2016 and January 2020. Demographic and clinical data were obtained from the electronic clinical records. Primary endpoints included both PFS and overall survival (OS). Early neutropenia was defined as the nadir absolute neutrophil count (ANC) during the first two cycles of treatment. PFS and OS were analysed with Kaplan–Meier survival curves comparing neutropenia grades using the log rank test to check differences between survival curves. Multivariate Cox proportional hazard regression model was also used to predict OS. Results: A total of 61 patients were included. Demographic and clinical characteristics are shown in table 1 . 28 patients (45.9%) stopped treatment and 24 (85.7%) discontinued due to progression. 25 patients (41.0%) required ≥1 dose reduction. In the first two cycles, 54 patients (88.5%) experienced grade 1–4 neutropenia. Patients who experienced grade 2–4 neutropenia in the first two cycles were associated with significantly prolonged median OS (log rank p=0.019). However, there was no significant association with prolonged median PFS (log rank p=0.572). After adjusting for potential cofounders (baseline ACN, age and weight), grade 2–4 neutropenia remained significantly and independently associated with prolonged OS (HR 0.26, 95% CI 0.09 to 0.77, p=0.015). Conclusion and relevance: Early neutropenia was significantly associated with a prolonged OS, supporting the suggestion that neutropenia could be a pharmacodynamic marker for palbociclib dosing. References and/or acknowledgements: McAndrew NP, et al . Br J Cancer 2020;123 :912–18. Conflict of interest: No conflict of interest